Integrated design of emulsified cosmetic products: coupling a multi-scale approach with population balance modeling (2023)
Chemical product design has become an active area of research within the chemical industry in response to an increasingly demand for consumer-oriented products. The era of globalization has intensified competition generating strong market forces that play an essential role in the chemical industry. Consequently, the chemical product industry has moved from the production of bulk commodities products towards higher value-added products, placing particular interest in the manufacture of specialty chemicals and consumer-oriented products such as emulsified products. Emulsions are thermodynamically unstable colloidal systems, in which there are droplets of a liquid dispersed in a second immiscible fluid. The use of emulsions in industry has a vast number of applications at different sectors, such as cosmetic, food, petrochemical, pharmacy, biotechnology and nanotechnology, leading to a great interest to understand the relationship between the formulation, the process variables and the properties of these systems. A multi-scale approach, whose primary purpose is to understand the links between the different temporal and spatial scales within a system and its overall impact on a finished product, is an appropriate way to study these relationships at different levels. As highlighted in previous studies, these links are key for the design and development of new products. The design process for chemical products could be addressed using different solution strategies, such as experiment-based (trial-and-error), model-based, and integrated approach. Recent studies have drawn particular attention to the application of an integrated approach to manage the design process of chemical products, for instance, emulsions The integrated approach is the most appropriate compared to classical design methodologies such as trial-and-error and model-based approaches since higher efficiency and reliability can be achieved at manufacturing an emulsified product. In this respect, it is worth mentioning the current need for dealing with the design of emulsified cosmetic products from an integral perspective, relating elements of the multi-scale approach of emulsion properties with the formulation and the process involved in the manufacturing of these systems. However, most of these products are still designed using heuristic or even artisanal considerations. Consequently, an active area of research in this field is focused on the product properties, formulation, and preparation of emulsions through an integrated approach. In particular, studies have used model-based techniques to predict the properties of emulsions. Most of these studies have focused on the calculation of emulsion properties (e.g., viscosity) using an average value of the drop diameter rather than considering the actual droplets size distribution (DSD). DSD for emulsions can be predicted using Population Balance Models (PBMs). PBM is a proven method and represents a comprehensive modeling framework for the description of the dynamics of properties characterized by distributions, as it is the case for emulsions droplets diameter. Although considerable attention has been devoted to the study and implementation of PBMs in emulsions, there is a lack of studies linking this modeling framework with the integrated design approach of emulsified cosmetic products. This coupling would represent a new feature for the implementation of integrated design strategies for emulsified products since the DSD has a significant effect on emulsified product properties and stability. Based on the above, this work performs an integrated design approach for emulsified cosmetic products. This approach utilizes model-based design techniques within a multiscale framework. In this study, the integrated design approach covers key elements for emulsified products: product formulation and composition, process operational conditions, product properties at different scales, the implementation of a Population Balance Model to couple the DSD for the estimation of product physical properties, as well as the consideration of consumer preference and economic criteria. These components are employed to formulate and solve an optimization problem aimed at achieving the optimal product formulation. Through this approach, we gain valuable insights into the interconnections between product properties at different scales, product formulation, operational conditions, and the product's performance in the market.